Effect of Aperture shape on Visibility of Quantum Cryptography System - Haider, Adawiya J.; Hassan, Azhar I.; Addie, Ali J. (Nahrain University College of Engineering Journal, 2008)
The main goal in Quantum Cryptography is high security and this can be achieved by using single photon sources, thus we have studied the entangled photon source and how the coincident count rate and visibility could be affected by the optical elements of the system setup. The present work is a theoretical analysis devoted to investigate the interference pattern of biphoton amplitude generated by spontaneous parametric down conversion (SPDC) in a nonlinear crystal (BBO) pumped by femto-second optical pulses. We have studied the visibility as a function of optical path delay for different parameters, such as the crystal length, aperture diameter, size and shape of the aperture The shape of interference pattern can be enhanced by using different shapes & sizes of aperture. So in the case of continuous wave ( CW )pumping, when using circular aperture the visibility is highest and symmetry shape occurs at lower aperture diameter (b=0.5mm). Asymmetry and wide dip pattern is occurred at larger aperture diameter (b=10mm), when using shifting ring, a negative peak was appeared. In case of pulsed pump asymmetry, patterns occur and increase with increase of crystal length and decreasing aperture diameter. When using slit aperture (vertical and horizontal direction), the coincident count is more symmetric in horizontal with dimension (1x7) mm. All the results of this work are based on several numerical techniques and different programming codes. For example, adaptive Simpson quadrator method have been used to numerically evaluate the double integral in some equations. And adaptive Lobatto quadrator method has been used to numerically evaluate a single integrals. The later method is more efficient when required a high accuracy or a smooth integral